HPLC-EICD: An Useful Tool for the Pursuit of Novel Analytical Strategies for the Detection of Antioxidant Secondary Metabolites - Castro-Gamboa, Ian [UNESP]; Cardoso, Carmen L. [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Cavalheiro, Alberto José [UNESP]; Furlan, Maysa [UNESP]; Bolzani, Vanderlan da Silva [UNESP] (FapUNIFESP (SciELO), 2003)
Living cells are continuously exposed to a variety of challenges that exert oxidative stress and are directly related with senescence and the onset of various pathological conditions such as coronary heart disease, rheumatoid arthritis and cancer. Nevertheless, living organisms have developed a complex antioxidant network to counteract reactive species that are detrimental to life. With the aim of bio-prospecting plant species from the Brazilian Cerrado and Atlantic Forest, we have established a methodology to detect secondary antioxidant metabolites in crude extracts and fractions obtained from plant species. Combining HPLC with an electrochemical detector allowed us to detect micromolecules that showed antioxidant activities in Chimarrhis turbinata (DC) leaf extracts. Comparison with purified flavonoid standards led us to identify the compounds in their natural matrices giving valuable information on their antioxidant capacity.
Keywords: Antioxidant; Flavonoids; HPLC-EICD; Reactive-oxygen-species; antioxidant; Chimarrhis turbinata extract; flavonoid; plant extract; unclassified drug; antioxidant activity; Chimarrhis turbinata; controlled study; drug purification; electrochemical detection; high performance liquid chromatography; medicinal plant; nonhuman; oxidative stress; Rubiaceae; senescence; technique